Modified Relative Dose Response (MRDR) Survey | Olawale Olaniyan - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
In this video, Olawale Olaniyan, a laboratorian for the MRDR survey explains that a proper orientation about the MRDR test was given to the respondents which led to a positive response from them. He further explained that they were chosen randomly based on some selection criteria including good hemoglobin levels. Therefore, 'the goal of this survey is to make the respondents accept you irrespective of their belief and their keen participation which is a major thrive.